2008
DOI: 10.1080/08990220802131234
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Merkel cells in the monkey skin: An anatomical model

Abstract: The Merkel cell-neurite complex is considered to be one class of mechanoreceptors in the skin. Merkel cells are innervated by slowly adapting type I (SAI) tactile nerve fibers. In this paper, the detailed distribution of Merkel cells is studied by immunohistochemical labeling of the monkey (Macaca fascicularis) digital glabrous skin. Specific morphometric variables (density of intermediate epidermal ridges and Merkel cells, distance between skin surface and ridge tips and bases, maximum and average cell counts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…The fingertip, for instance, has greater SA1 density (Johansson and Vallbo, 1979), smaller SA1 receptive fields (Schady and Torebjörk, 1983), and correspondingly better spatial acuity than does the finger base (Gibson and Craig, 2002). Anatomical (Güçlü et al, 2008) and physiological (Johansson, 1978) evidence suggests that SA1s branch to innervate several clusters of Merkel cells (Fig. 4a).…”
Section: Discussionmentioning
confidence: 99%
“…The fingertip, for instance, has greater SA1 density (Johansson and Vallbo, 1979), smaller SA1 receptive fields (Schady and Torebjörk, 1983), and correspondingly better spatial acuity than does the finger base (Gibson and Craig, 2002). Anatomical (Güçlü et al, 2008) and physiological (Johansson, 1978) evidence suggests that SA1s branch to innervate several clusters of Merkel cells (Fig. 4a).…”
Section: Discussionmentioning
confidence: 99%
“…Guclu speculated that SAI afferents innervate multiple Merkel cells so SAI afferents can continue responding to stimuli despite the loss of one or more of these biological [9]. While focused on artificial sensors, the work presented here suggests that a compound sensor such as the SAI end organ would gain the most durability from its multiple transducers if they were matched to spike encoders in a one-to-one relationship.…”
Section: Discussionmentioning
confidence: 95%
“…These multiple spike encoders are thought to reset each other, i.e., a spike generated at any spike encoder antidromically propagates to all other spike encoders, initiating absolute refractory periods and restarting the process of spike initiation [8]. A likely benefit of the SAI end organ’s compound nature has been suggested as increasing the durability of the natural mechanosensory unit [9]. …”
Section: Introductionmentioning
confidence: 99%
“…This is not the case. One explanation would be that it has been suggested that the SA characteristic of Merkel cell afferents might be the result of a population code carried by large clusters of Merkel cells [e.g., GüÇlü et al (2008)]. Moreover, it is known that the sustained portion of the Merkel cell afferent response in mice results from the contributions of many Merkel cells (Maksimovic et al 2014).…”
Section: Airflow Responses In Bat S1mentioning
confidence: 96%